Caracterização genômica dos profagos e elementos parecidos com profagos nas bactérias láticas do gênero Weissella - Cesar da Silva Santana Moura (2023)
Lactic acid bacteria (LAB) constitute a group of microorganisms widely distributed in food and the microbiota of humans and animals. Over the decades, these bacteria have played a fundamental role in the food industry, serving as essential fermenting cultures. More recently, they have emerged as probiotic agents, offering health benefits to humans. The genus Weissella, belonging to LAB, does not yet have members characterized as probiotics. Despite this, it stands out as an intriguing research area, as some of its strains have shown potential to be characterized as probiotics. Nevertheless, the characterization of their prophages, which play a vital role in gene transfer and the modulation of microbial communities, has remained notably underexplored. In this study, we adopted a comprehensive approach that included 313 genomes available at the National Center for Biotechnology Information (NCBI) and the sequencing, annotation, and functional analysis of the genomes of three new Weissella strains: Weissella cibaria 1BM, Weissella confusa GIR46L4, and Weissella paramesenteroides V3B-11. Our results revealed an intriguing feature of Weissella: restriction-modification systems, such as RM/DRUANTIA/DISARM, which play a vital role in defense against phages. These systems promote coevolution between bacteria and phages, facilitating the incorporation of prophages and viral genes into their genomes and modifying existing prophages. This dynamic is crucial for the survival of these bacteria in challenging environments and their ability to compete effectively with other bacterial species. Another relevant aspect addressed was the analysis of the CRISPRCas system. We detected variations in its occurrence and effectiveness among different Weissella species. The genus generally presents less developed CRISPR-Cas systems, with the notable exception of the Weissella soli species, which exhibited two distinct subtypes of this system. However, the limited number of spacers in some species suggests a potential limitation in their ability to combat phages. Additionally, we identified the preservation of specific prophages in different Weissella species, highlighting the richness and complexity of the genetic diversity present in these microorganisms. Concerning antibiotic resistance, our investigation did not find genes with high identity representing a significant risk of horizontal gene transfer. Most virulence genes shared similarities with structural viral genes but lacked high identity. We also identified viral proteins with potential biomedical applications, expanding the possible uses of these microorganisms. In summary, this study provides a deeper understanding of prophages in Weissella bacteria, highlighting their role in bacterial evolution and pointing to relative safety regarding the dissemination of clinically important genes. This study addresses a gap in research related to the Weissella genus, its prophages, and their biological implications. Given the increasing relevance of LAB and phages, as well as the interest in the biotechnological potential of Weissella, our goal was to contribute to the classification of the genus as GRAS (Generally Recognized As Safe) or QPS (Qualified Presumption of Safety) status. This approach offers important insights into phage-bacteria interactions, with significant implications for the safety and biotechnological applications of Weissella.